(untitled) (Perspectivas de las Ciencias Económicas y Jurídicas, 2022)
The book "Legal sociology and childhood" is the result of work carried out by two UBACYT research teams, led by Professor Dra. Laura Lora and based at the Ambrosio L. Gioja Institute of Legal and Social Research of the Law School of the Buenos Aires’ University. The work is divided into three parts (Legal Sociology; Access to Justice and Gender and Identity) and has ten chapters from which these issues are addressed from different perspectives that call for reflection on a very pressing issue such as childhood.